2006
DOI: 10.1038/ni1326
|View full text |Cite
|
Sign up to set email alerts
|

The generation of protective memory-like CD8+ T cells during homeostatic proliferation requires CD4+ T cells

Abstract: Antigen-specific memory T cells are a critical component of protective immunity because of their increased frequency and enhanced reactivity after restimulation. However, it is unclear whether 'memory-like' T cells generated during lymphopenia-induced homeostatic proliferation can also offer protection against pathogens. Here we show that homeostatic proliferation-induced memory (HP-memory) CD8(+) T cells controlled bacterial infection as effectively as 'true' memory CD8(+) T cells, but their protective capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
207
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(219 citation statements)
references
References 43 publications
10
207
1
1
Order By: Relevance
“…Moreover, it has been shown recently that TRAIL is a key negative regulator of secondary CD8 ϩ T cell responses. Specifically, TRAIL-deficient helpless memory CD8 ϩ T cells (i.e., CD8 ϩ T cells that mature in the absence of adequate CD4 ϩ T cell help) and TRAIL-deficient CD8 ϩ T cells undergoing homeostatic proliferation both exhibit increased proliferation and have a survival advantage compared with TRAIL-intact CD8 ϩ T cells during secondary immune responses (58,59). In the P3 F 1 model, B cell elimination has been shown to be a sensitive measure of the ability of naive CD8 ϩ T cells to become CTL effectors (36); thus, the enhanced CD8 ϩ CTL function exhibited by TRAIL KO donor cells supports the idea that in contrast to the positive regulatory role for CD4 ϩ cells, TRAIL may also negatively regulate CD8 ϩ proliferation in a primary Ag-induced response, particularly in the setting of suboptimal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown recently that TRAIL is a key negative regulator of secondary CD8 ϩ T cell responses. Specifically, TRAIL-deficient helpless memory CD8 ϩ T cells (i.e., CD8 ϩ T cells that mature in the absence of adequate CD4 ϩ T cell help) and TRAIL-deficient CD8 ϩ T cells undergoing homeostatic proliferation both exhibit increased proliferation and have a survival advantage compared with TRAIL-intact CD8 ϩ T cells during secondary immune responses (58,59). In the P3 F 1 model, B cell elimination has been shown to be a sensitive measure of the ability of naive CD8 ϩ T cells to become CTL effectors (36); thus, the enhanced CD8 ϩ CTL function exhibited by TRAIL KO donor cells supports the idea that in contrast to the positive regulatory role for CD4 ϩ cells, TRAIL may also negatively regulate CD8 ϩ proliferation in a primary Ag-induced response, particularly in the setting of suboptimal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CD4 þ Th cells are required during the maintenance phase of long-lived CD8 þ memory T cells (Sun et al, 2004). Regulation of tumor-necrosis factor-related apoptosis-inducing ligand expression in CD8 þ T cells accounts for the role of CD4 þ T cells in the generation and expansion of memory and memory-like CD8 þ T cells (Janssen et al, 2005;Hamilton et al, 2006). However, the presence of CD4 þ Treg cells and the newly discovered IL-17-producing T cells (Th17) may change our thinking about the role of CD4 þ T cells in cancer and many other diseases.…”
Section: Cd4 þ Th17 and Treg Cells In Cancermentioning
confidence: 99%
“…Lastly, another distinctive feature of CD8 + T M cells is their ability to robustly produce cytokines and kill infected target cells within hours following stimulation. This contrasts with their T N -cell precursors, which require replication and differentiation over several days to achieve the same functional capacity [22,25,26]. Together, heightened precursor frequency, expanded anatomical distribution, enhanced proliferative capacity and rapid recall ability comprise the hallmark attributes of protective CD8 + T M cells.…”
mentioning
confidence: 91%
“…Importantly, like T M cells formed after acute pathogenic infections, several groups have shown that CD8 + T M cells generated via LIP have cytotoxic ability, can efficiently upregulate production of effector cytokines and chemokines following stimulation and are capable of robust proliferation after Ag challenge in vivo [25,29,30]. Moreover, these cells are dependent on the presence of helper CD4 + T cells (CD4 + T H ) for normal differentiation, a requirement shared with CD8 + T M cells generated by acute infections [25,31,32].…”
Section: Lymphopenia-induced Proliferationmentioning
confidence: 99%
See 1 more Smart Citation